2017
DOI: 10.1186/s13104-016-2345-3
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of genes related to gain and intake in the liver of beef cattle

Abstract: BackgroundTo better understand which genes play a role in cattle feed intake and gain, we evaluated differential expression of genes related to gain and intake in the liver of crossbred beef steers. Based on past transcriptomics studies on cattle liver, we hypothesized that genes related to metabolism regulation and the inflammatory response would be differentially expressed. This study used 16 animals with diverse gain and intake phenotypes to compare transcript abundance after a 78 day ad libitum feed study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
200
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(247 citation statements)
references
References 21 publications
37
200
9
1
Order By: Relevance
“…Although the RFI values pertaining to the animals used in this study showed clear signi cant divergence between high and low-RFI groups in both heifers and bulls, we failed to identify any DEGs within the liver tissue of the heifers and the skeletal muscle tissue of the bulls. Similarly, other studies evaluating the molecular control of RFI divergence in crossbred steers reported no DEGs following correction for multiple testing [29][30][31]. Therefore the main observation of the current study is the inconsistent effect of RFI across (i) gender and (ii) tissue for DEG pro les despite a 10% and 15% difference in DMI between high and low RFI heifers and bulls, respectively, with no difference in ADG in the current study.…”
Section: Discussionsupporting
confidence: 62%
“…Although the RFI values pertaining to the animals used in this study showed clear signi cant divergence between high and low-RFI groups in both heifers and bulls, we failed to identify any DEGs within the liver tissue of the heifers and the skeletal muscle tissue of the bulls. Similarly, other studies evaluating the molecular control of RFI divergence in crossbred steers reported no DEGs following correction for multiple testing [29][30][31]. Therefore the main observation of the current study is the inconsistent effect of RFI across (i) gender and (ii) tissue for DEG pro les despite a 10% and 15% difference in DMI between high and low RFI heifers and bulls, respectively, with no difference in ADG in the current study.…”
Section: Discussionsupporting
confidence: 62%
“…Amongst the differences identified were the poor knowledge on bTB transmission to people, consumption of uninspected meat and the habit of drinking raw milk during milking, implying that the herdsmen are more at risk of M. bovis infection. Several investigations have reported the potential risk of bTB transmission through drinking of raw milk and contact with infected cattle [48][49][50]. Poor practices regarding TB have been reported amongst high risk groups such as the herdsmen and M. bovis transmission to people was confirmed in a study of livestock workers in Nigeria [35,51].…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that heterogeneity among the Leishmania parasites in different endemic regions may cause differences in the immune responses of infected hosts [53]. Therefore, despite the good performance of rK39-ICT, the limitations of this test are low sensitivity and poor specificity in some of the regions endemic for VL [51,54]. Bhattacharyya et al showed that genetic diversity, and a polymorphism in the sequence of rK39 occurring in East Africa and South Asia, influence the performance of rK39-based assay [55].…”
Section: Elisa Testmentioning
confidence: 99%